Explorar los límites : arte y arquitectura en las exposiciones de las vanguardias - Paz Agras, Luz (Textos de arquitectura y diseño., 2015)
The avant-garde movements of the early 20th century find exhibitions are an opportunity to experiment with the relationship between the artistic object and space. The exhibition proposals become true architectural projects that act as laboratories of ideas in which different artistic disciplines interact directly. The spectator plays an active role in the perception of the artistic object. From the spectator's presence in the exhibition, they can test new spatial concepts by assimilating, in some cases explicitly, the concept of user-inhabitant. Through proposals by authors such as El Lissitzky, Moyoly-Nagy, Kiesler or Duchamp, a tour of the architectural findings of their expository experiences, all of them contagious from the atmosphere of creative effervescence and full of confidence in the technique and progress that was experienced in the western world in the interwar period. Some of these concepts remain in contemporary creation, where they continue to preserve the experimental spirit and betting on a dialogue between distinct disciplines, a crucial issue in contemporary architecture.